A Review of Technologies and Evaluation Softwares for Distributed Energy Source System. (6th January 2016) - Gao, Yanna; Meng, Xi; Gao, Weijun; Long, Enshen
Abstract: This study reviews the technologies and evaluation softwares for the Distributed Energy Resource System (DERs), which is considered as a realistic and economical way to realize the clean utilization of energy. For the the technologies of DERs, there summarizes the characteristics and global development of CHP (Combined Heat and Power), renewable generation, energy storage and cell fuels. In addition, this study sums up 15 kinds of softwares for evaluating DERs from the aspects of their developers, application scope, properties and so on. The results in this study provide the necessary information for the technologies and evaluation softwares for designing and optimization of DERs.